2000
DOI: 10.1099/0022-1317-81-6-1453
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A responses to Puumala hantavirus

Abstract: Puumala hantavirus (PUUV) causes nephropathia epidemica (NE), a form of haemorrhagic fever with renal syndrome that occurs in northern and central Europe. The immunoglobulin A (IgA) response in NE patients was studied. The levels of total serum IgA in acute-phase samples from NE patients were found to be significantly elevated when compared with the levels in healthy controls. ELISAs for detection of the IgA1 and IgA2 responses against each PUUV structural protein (N, G1 and G2) were developed and evaluated. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…For one patient without detectable IgM, the evidence of acute infection was confirmed by IgA detection accompanied by increasing IgG titers in follow-up. In previous studies, another MAb capture IgA ELISA (specificity 100%) was found to detect 91% of IgM anti-N-positive sera used (8). In agreement with previous observations (8,12,15,34), the N-specific IgA response has been found to be decreased in convalescent-and late-convalescent-phase sera.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…For one patient without detectable IgM, the evidence of acute infection was confirmed by IgA detection accompanied by increasing IgG titers in follow-up. In previous studies, another MAb capture IgA ELISA (specificity 100%) was found to detect 91% of IgM anti-N-positive sera used (8). In agreement with previous observations (8,12,15,34), the N-specific IgA response has been found to be decreased in convalescent-and late-convalescent-phase sera.…”
Section: Discussionsupporting
confidence: 73%
“…In previous studies, another MAb capture IgA ELISA (specificity 100%) was found to detect 91% of IgM anti-N-positive sera used (8). In agreement with previous observations (8,12,15,34), the N-specific IgA response has been found to be decreased in convalescent-and late-convalescent-phase sera. However, particularly for certain DOBV-infected patients, a persistence of IgM and/or IgA antibodies was observed in four persons (three of them IgM positive and three of them IgA positive) even until the end of the observation period of 2 to 3 years.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, IgA antibodies, like IgM antibodies, are markers of an early stage in infection [143]. Similar observations have been made for other viruses which primarily infect mucosal surfaces including measles-, rota-, and enteroviruses [144,[144][145][146].…”
Section: Iga Responsementioning
confidence: 55%
“…An alternative way that has been used to diagnose acute/recent PUUV infection is to demonstrate low-avidity IgG antibodies (eluted by 8 M urea), either in an immunofluorescence test or enzyme immunoassay [22,23]. Acute-phase PUUV and ANDV patients also develop IgA 1 antibodies at least to the N protein [20,24], but this has not been applied to routine diagnostics. In addition, PUUV infection induces low levels of specific IgE antibodies but without correlation to clinical parameters [25].…”
Section: Implications For Serodiagnosticsmentioning
confidence: 99%
“…after the first week after onset of NE [38][39][40]. Possible viral persistence has been suggested, since high levels of PUUV-specific IgG 4 and of IgA 1 antibodies [24,41], which characterize many chronic human viral infections, such as hepatitis B and herpes group virus infections, are seen in late convalescent serum samples.…”
Section: Other Characteristics Of the Humoral Antibody Responsementioning
confidence: 99%